Rough Planning of Melaka Malay City Before 1511 Based on Portuguese Sources - Kosman, Kamarul Afizi; Mokhtar, Noor Aisyah (International Journal of Psychosocial Rehabilitation, 2020)
The Empire of the Malay Sultanate of Melaka is often referred to as an imposing and glorious empire of various administrative, economic, and physical aspects. The Melaka Malay City in the context of this paper refers to Bandar Melaka during the reign of the Melaka Malay Sultanate, which was originally from Bukit Melaka which houses Melaka Palace to the surrounding area. The purpose of this study is to examine and interpret the picture of the Melaka City based on the sources of Portuguese sketches and drawings which are believed as valid. The method focused in this paper is through debates on sketches and drawings obtained, then contrasted and combined with historical records relating to Melaka City or events related to the sketches and paintings. This research is a bit of a story, as well as describing the Melaka Malay Sultanate era before the Portuguese’s conquest in terms of environmental, physical, and other related aspects. The implications of this study can be a catalyst for continuous and deeper research to know about Melaka City and skyline during the era of the Malay Sultanate. The study showed that the plan of Melaka city was not a planned city plan since the reign of the first Sultan of Melaka, but was a city that grows organically according to the current and growing needs of the Melaka Malay Empire. The layout features of the Melaka City are in line with its function as an entrepot city, hence the municipal rough plan match and resemble the picture of paintings and sketches described in most historical records. In conclusion, the Melaka Malay City before the Portuguese’s conquest was likely to be a physical civilization and should be examined and explicitly evidenced in rebuilding the Melaka Malay civilization that had long been established.